Ginsenoside Rh2 Downregulates LPS-Induced NF-κB Activation through Inhibition of TAK1 Phosphorylation in RAW 264.7 Murine Macrophage. (17th February 2013) - Lian, Li-Hua; Jin, Quan; Song, Shun-Zong; Wu, Yan-Ling; Bai, Ting; Jiang, Shuang; Li, Qian; Yang, Ning; Nan, Ji-Xing
Abstract : The present study was carried out to evaluate the inhibitory effects of ginsenoside Rh2 on nuclear-factor- (NF-) κ B in lipopolysaccharide- (LPS-) activated RAW 264.7 murine macrophages. RAW 264.7 cells were pretreated with indicated concentrations of ginsenoside Rh2 for 1 h prior to the incubation of LPS (1  μ g/mL) for indicated time period. Ginsenoside Rh2 reduced CD14 and Toll-like receptor 4 (TLR4) expressions 24 h after LPS stimulation. Furthermore, ginsenoside Rh2 significantly inhibited TGF-beta-activated kinase 1 (TAK1) phosphorylation 30 min after LPS stimulation. Ginsenoside Rh2 was further shown to inhibit NF- κ B p65 translocation into the nucleus by suppressing I κ B- α degradation. Also, LPS increased mRNA expression of TNF- α and IL-1 α time-dependently, while TQ reduced TNF- α within 3 h and IL-1 α within 1 h. And we firstly found that pretreatment of ginsenoside Rh2 successively inhibited hypoxia-inducible factor- (HIF-) 1 α expression increased by LPS. In conclusion, ginsenoside Rh2 may inhibit LPS-induced NF- κ B activation and reduce HIF-1 α accumulation, suggesting that ginsenoside Rh2 may be considered as a potential therapeutic candidate for chronic inflammatory diseases.